2013
DOI: 10.1002/ett.2718
|View full text |Cite
|
Sign up to set email alerts
|

Joint relay‐pair selection for buffer‐aided successive opportunistic relaying

Abstract: In this work, we present a buffer-aided successive opportunistic relaying scheme that aims at improving the average capacity of the network when inter-relay interference arises between relays that are selected for simultaneous transmission and reception. We propose a relay selection policy that, by exploiting the benefits of buffering at the relays, decouples the receiving relay at the previous time slot to be the transmitting relay at the next slot. Furthermore, we impose an interference cancellation threshol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 31 publications
0
34
0
Order By: Relevance
“…Note that in the case, for which at a slot the network operates in a single-link mode, CSI acquisition is triggered in the next slot. The selection process described by (8) assures that CSI acquisition is avoided as long as full-duplexity is achieved at a power cost which is not higher than Z. This scheme trades-off complexity reduction for performance degradation in terms of power reduction and allows the network to be configured in a variety of ways.…”
Section: B Suboptimal Full-duplex Relaying With Max − Link Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that in the case, for which at a slot the network operates in a single-link mode, CSI acquisition is triggered in the next slot. The selection process described by (8) assures that CSI acquisition is avoided as long as full-duplexity is achieved at a power cost which is not higher than Z. This scheme trades-off complexity reduction for performance degradation in terms of power reduction and allows the network to be configured in a variety of ways.…”
Section: B Suboptimal Full-duplex Relaying With Max − Link Selectionmentioning
confidence: 99%
“…(8), Z can be split into two power levels, namely Z 1 and Z 2 (i.e., Z 1 + Z 2 = Z): one for the SR k link and one for the R k D link. For the R k D link, since there is no interference, the condition is fulfilled if P * Rj ≤ Z 2 .…”
Section: Remarkmentioning
confidence: 99%
See 1 more Smart Citation
“…Simple schemes, where an SN stores and carries the information until favorable communication conditions with the destination node are found, have been shown to reduce energy consumption [11]. The studies reported in [12,13] also highlight the benefits of opportunistically exploiting the buffering capabilities at the relays to improve the average capacity and efficiency of the network. Opportunistic networking can also help offloading data traffic from cellular networks to metropolitan WiFi access points without degrading the QoS [14].…”
Section: Related Workmentioning
confidence: 99%
“…Equation (13) indicates that the PER augments with the distance (d in meters) between transmitter and receiver [despite using more robust modulation and coding schemes (12)], although an upper PER limit (0.75) is reached. The IEEE 802.11g channel efficiency (Eff ) represents the effective time that the 802.11g channel is used to transmit data, and depends on the transmission time of data packets .t d / and acknowledgement (ACK) packets .t ack /, the contention period .t cont / and the inter-frame guard times (DIFS and SIFS) [22]:…”
Section: Evaluation Scenariomentioning
confidence: 99%